The Prevalence of Non-communicable Diseases Among HIV Patients Receiving ARV Treatment at the Outpatient Clinic, Thanh Khe Regional Medical Center, Da Nang - Thi Huyen, Pham; Song Hieu, Nguyen; Xuan Phuong, Nguyen; Vu Thuy, Bo Thi; Khanh Duy, Nguyen; Thuy Linh, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Objective: To assess the prevalence of non-communicable diseases and related factors among HIV patients receiving ARV treatment at the Outpatient Clinic, Thanh Khê Regional Medical Center, Da Nang. Subjects and Methods: A cross-sectional descriptive study was conducted on 300 patients who were being treated and managed at the Outpatient Clinic of Thanh Khê Regional Medical Center from May to August 2025. Results: The mean age of the participants was 38.16 years, with the most common age group being 30–40 years. The majority were male (76.7%). The average duration since HIV diagnosis was 6.6 ± 5.2 years, and the mean duration of HIV treatment was 75.4 ± 60.6 months. The most recent mean CD4 count was 573.2 ± 240.7 cells/mm³. The prevalence of hypertension was 1.3%, diabetes 1.7%, dyslipidemia 26.7%, and overweight/obesity 36.0%. There was a significant association between age, income, alcohol consumption, processed food intake, and overweight/obesity, as well as between alcohol consumption and dyslipidemia. Conclusion: The prevalence of hypertension and diabetes among HIV patients receiving ARV treatment was relatively low; however, the rates of dyslipidemia and overweight/obesity were notably high. Therefore, management should focus on lipid disorders and weight control, along with counseling on reducing alcohol consumption and limiting processed foods for at-risk groups.